2022
DOI: 10.3390/molecules27031066
|View full text |Cite
|
Sign up to set email alerts
|

AQP4 Attenuated TRAF6/NFκB Activation in Acrylamide-Induced Neurotoxicity

Abstract: Acrylamide (ACR) is present in high-temperature-processed high-carbohydrate foods, cigarette smoke, and industrial pollution. Chronic exposure to ACR may induce neurotoxicity from reactive oxygen species (ROS); however, the mechanisms underlying ACR-induced neurotoxicity remain unclear. We studied 28-day subacute ACR toxicity by repeatedly feeding ACR (0, 15, or 30 mg/kg) to rats. We conducted RNA sequencing and Western blot analyses to identify differences in mRNA expression in the blood and in protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…This raises the possibility that KA mitigates BU‐induced neurotoxicity by regulating TRAF6. Moreover, it is widely recognized that inhibition of the TRAF6/NF‐κB pathway is an efficient way to protect against neurotoxicity 23 . Thus, the levels of TRAF6 and NF‐κB‐related proteins (NF‐κB‐p65 and p‐NF‐κB‐p65) were determined by western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This raises the possibility that KA mitigates BU‐induced neurotoxicity by regulating TRAF6. Moreover, it is widely recognized that inhibition of the TRAF6/NF‐κB pathway is an efficient way to protect against neurotoxicity 23 . Thus, the levels of TRAF6 and NF‐κB‐related proteins (NF‐κB‐p65 and p‐NF‐κB‐p65) were determined by western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is widely recognized that inhibition of the TRAF6/NF-κB pathway is an efficient way to protect against neurotoxicity. 23 Thus, the levels of TRAF6 and NF-κB-related proteins (NF-κB-p65 and p-NF-κB-p65) were determined by western blotting. As indicated in Figure 5A, BU stimulation led to an increase in the TRAF6 protein level; however, such an increase was reversed with the increase in the KA concentration.…”
Section: Ka Reverses Bu-induced Traf6 Upregulation and Nf-κb Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results in this study showed ACR-induced neurotoxicity the same as previously reported that rodents treated with 30 mg/kg ACR developed certain symptoms of neurotoxicity, such as limb numbness, muscle weakness, and foot drop. 23,27 Using gait observations for the neurotoxicity index is bined with increased rearfoot extension on landing, reduced hind limb grip, and extensor thrust. 25 Similar symptoms were observed in Wistar rats treated with the same dose of ACR for 28 days.…”
Section: Discussionmentioning
confidence: 99%